An impact study of COVID-19 on the electricity sector: A comprehensive literature review and Ibero-American survey. (April 2022) - Lazo, Joaquín; Aguirre, Gerson; Watts, David
Abstract: To stop the spread of COVID-19, governments have implemented confinement measures unprecedented in modern society. One of the main consequences has been the paralysis of commercial and industrial sectors worldwide, primary electricity consumers. This paper examines the impact of these measures on the electricity sector through a literature review accompanied by fieldwork on the impact of COVID-19 in Ibero-America and its energy regulatory response. First, we will review the causes of the reduction in electricity demand due to the confinement measures and their technical and financial consequences in the electricity sector. Second, we will examine the impact of COVID-19 on the wind and solar PV energy sectors, mainly affected by the paralysis of production and export of materials and components. Third, we will revise the regulatory measures implemented by the countries to avoid the interruption of electricity supply to households. This paper will end by reviewing economic recovery plans and their relationship to the energy transition. Although there are no fundamental differences between developed and developing countries in their regulatory reaction to this crisis in the energy sector, there are significant differences in economic recovery planning. While developed countries aim for a green economic recovery and the creation of green jobs, developing countries are allocating least resources to social protection and general economic stimulus programs, postponing climate objectives. In Latin America, this adds to the high levels of debt faced by utilities and the possible resurgence of social crises that were stopped by the COVID-19 outbreak, making a green recovery even more difficult. Graphical abstract: Image 1 Highlights: The reduction in electricity demand has caused technical challenges in the grid. Electric utilities are facing growing and long-term financial problems. Renewable energy projects have been delayed and financially harmed. The measure to ban disconnection for non-payment has been implemented worldwide. Latin American social crisis tempered by COVID-19 could hinder economic recovery.